Life of Pi [videorecording (Blu-Ray + DVD)] - Netter, Gil; Lee, Ang, 1954-; Womark, David; Magee, David, 1962-; Sharma, Suraj, 1993-; Khan, Irrfan, 1967-2020; Tabu, 1970 November 4-; Spall, Rafe, 1983-; Depardieu, Gérard, 1948-; Martel, Yann (20th Century Fox Home Entertainment, 2013)
Emotional thematic content throughout and some scary action sequences and peril.